Intrauterine device continuation rates and reasons for discontinuation in a Central European clinic with a high standard of care and ultrasound follow-up: a retrospective cohort study. (2nd November 2018) - Bachofner**, Marion; Blickenstorfer**, Kerstin; Hutmacher, Juliane; Wehrle, Lucia; Leeners, Brigitte; Merki-Feld, Gabriele
Abstract: Objectives: The aims of the study were to conduct an analysis of intrauterine device (IUD)-related outcomes, including continuation rates, reasons for discontinuation, rates of dislocation and risk factors for dislocation, in a clinical setting with regular ultrasound monitoring of the IUD position. Methods: A retrospective chart review was carried out of all IUD insertions over a period of 5 years. Results: A total of 755 IUDs were inserted over the study period. The overall observation time was 1572 woman-years. The removal rate was highest in the first year after insertion and did not differ between devices: the 52 mg levonorgestrel-releasing intrauterine system (LNG-IUS; 18%) and third generation copper-T (Cu-T) IUDs (20%). Most removals were related to dislocation; fewer dislocations were seen with the LNG-IUS compared with the Cu-T IUDs ( p < .001). More removals of the LNG-IUS were carried out because of amenorrhoea, pain and hormone-related adverse events (20% of all removals). The discontinuation rate was higher in young women (age <25 years; p < .03), demonstrating the limitations of long-acting reversible contraception in this age group. The dislocation rate for devices replaced after dislocation was 31% in women receiving a Cu-T IUD and 38% in women receiving an LNG-IUS. Conclusions: The first year after IUD insertion is crucial with regard to discontinuation. Most removals were attributed to dislocation and affected mainly younger women. Dislocations occurred more rarely in LNG-IUS users and the rate decreased over time. We recommend follow-up within the first 6-12 months, especially in young women. Structured counselling and consideration of risk factors for dislocation may reduce removal rates for adverse events and dislocations.